Pengembangan Materi Gambar Teknik Melalui Software AutoCAD Dalam Bentuk Pelatihan Bagi Guru-guru di SMK 5 Padang - yefriadi yefriadi; Ismail Ismail; Junaidi Asrul; Rahmi Berlianti; Roza Susanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Studying and understanding technological developments is also one of the teacher's obligations. Today , as a teacher, it is necessary to utilize media or applications to improve the quality of learning. The development of information technology and computers is now taking place very quickly. Almost all fields of work and activities around us are always associated with systems connected to information technology and the use of computers. So that mastery of computer applications is absolutely necessary for anyone who wants to complete a field of work or activity more easily and quickly. The field of Engineering expertise is currently experiencing very rapid development, especially in the field of product design and design optimization. In the industrial world, the design process for a product no longer uses conventional methods, but uses a computer facility through a design and optimization software which is commonly referred to as CAD (Computer Aided Design). Multinational manufacturing companies have applied this technology and one of them is the AutoCAD application which can facilitate the creation of technical drawing learning. Mastery of the AutoCAD software application is very important for vocational students, especially to welcome global competition that can be used for engineering drawing. The current problem faced by teachers is how to install and run the AutoCAD application. AutoCAD is application software that is widely used in the domestic and foreign industrial world, so learning this application will provide many benefits for teachers and students, especially at SMK 5 Padang.